Impact evaluation of merger decisions - Oliver Budzinski (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2011)
This paper provides a comparative analysis of methods for the empirical ex post evaluation of merger control decisions. It develops a competition-policy oriented framework of assessment criteria for the leading evaluation methods and applies them to structural modeling and simulation, differences-in-differences methods, event studies as well as survey-based methods. It concludes that a method-mix is recommendable, however, under the exclusion of event studies that fail to secure a minimum level of reliability regarding the evaluation results. Furthermore, it warns against overly optimistic expectations about the effects of systematic impact evaluations of merger decisions.
Keywords: C18; C54; L41; L40; K21; 330; empirical methods of industrial organization; merger control; competition policy; antitrust decisions; comparative analysis; Fusionskontrolle; Kartellrecht; Wettbewerbspolitik; Bewertung